The Contribution of Swedish International Development and Co-operation Agency (SIDA) into the implementation of Community Social Services Development Project - Zabieta, Alfredas (Socialinė teorija, empirija, politika ir praktika, 2001)
The goal of the paper is to present the content and implementation of “Community social services development” project. The project was executed in collaboration between Swedish International Development and Co-operation Agency (SIDA) and the Ministry of Social Security and Labour of the Republic of Lithuania. The main goal of the project was to construct the alternative social service system. The financial resources of SIDA were used to evaluate the project and to finance qualification improvement programs.
Keywords: Coloboration; Social services; SIDA; Ministry of Social Security and Labour of the Republic of Lithuania